LEGAL CERTAINTY OF THE ROYA CONSENSUS DEED ON THE LOST MORTGAGE CERTIFICATE RELATED TO THE PLACEMENT OF THE CONFISCATION OF THE STATE RECEIVABLE AFFAIRS COMMITTEE (PUPN) - Hamdiyah Hamdiyah (International Journal Labs, 2022)
Consensus deed is a statement of the loss of mortgage certificate made by a Notary in the form of an authentic deed as an administrative order requirement for the loss of mortgage certificate related to the placement of PUPN confiscation for the purpose of recording the abolition of mortgage rights the process of registering mortgage roya at the Land Office. For this reason, the author is interested in researching, what is the legal position of the Roya Consensus Deed on the lost mortgage certificate related to the confiscation of PUPN in the Roya Mortgage process ? And how is the legal certainty of the concession agreement deed on the lost mortgage certificate related to the placement of the PUPN confiscation ? The legal theory used in this research is Gustav Radbruch's legal certainty theory and the Stufenbau Theory authority theory. The method used in this research is normative juridical research, namely library law research or secondary data with primary, secondary and tertiary legal sources. As for the research approach that is used a statutory approach, a conceptual approach, an analytical approach, a case approach and a technique for collecting legal materials is carried out by identifying and taking an inventory of positive legal rules, book literature, journals and source materials other laws. For the technique of analyzing legal materials, it is carried out with legal (interpretation) grammatical interpretation and systematic interpretation. From the results of the research obtained : the legal position of the Roya Consensus deed is only as a replacement requirement for the lost mortgage certificate related to the placement of the PUPN confiscation in the registration process of Roya Mortgage in terms of administrative order at the Land Office, so that the legal position of the Roya Consent Deed cannot be equated with a mortgage certificate which has executive power.